The BE (2)-M17 neuroblastoma cell line: revealing its potential as a cellular model for Parkinson’s disease - Carvajal-Oliveros, Angel; Román-Martínez, Camila; Reynaud, Enrique; Martínez-Martínez, Eduardo (Frontiers in Cellular Neuroscience, 2024)
Parkinson's Disease is a pathology with a wide range of in vivo and in vitro models available. Among these, the SH-SY5Y neuroblastoma cell line is one of the most employed. This model expresses catecholaminergic markers and can differentiate and acquire various neuronal phenotypes. However, challenges persist, primarily concerning the variability of growth media, expression of dopaminergic markers, and a wide variety of differentiation protocols have been reported in the literature without direct comparison between them. This lack of standardized differentiation conditions impacts result reproducibility and makes it very difficult to compare the results obtained from different research groups. An alternative cellular model is the BE (2)-M17, derived from neuroblastoma, which exhibits a high basal expression of numerous dopaminergic markers such as tyrosine hydroxylase, VMAT2 and DAT. The BE (2)-M17 cells show neuronal properties, grows rapidly in conventional media, and can easily be differentiated to increase their dopaminergic phenotype. In this review, we will thoroughly explore the properties of the BE (2)-M17 cell line and discuss its potential as an excellent model for studying Parkinson's Disease.